A membraneless air-breathing hydrogen biofuel cell based on direct wiring of thermostable enzymes on carbon nanotube electrodes. Issue 35 (7th April 2015) - Lalaoui, Noémie; de Poulpiquet, Anne; Haddad, Raoudha; Le Goff, Alan; Holzinger, Michael; Gounel, Sébastien; Mermoux, Michel; Infossi, Pascale; Mano, Nicolas; Lojou, Elisabeth; Cosnier, Serge
Abstract : A membraneless air-breathing hydrogen biofuel cell. Abstract : A biocathode was designed by the modification of a carbon nanotube (CNT) gas-diffusion electrode with bilirubin oxidase from Bacillus pumilus, achieving high current densities up to 3 mA cm −2 for the reduction of O2 from air. A membraneless air-breathing hydrogen biofuel cell was designed by combination of this cathode with a functionalized CNT-based hydrogenase anode.